Influence of Food Quality and Quantity on Cannibalistic Behavior in Tribolium Castaneum Adults Towards Larvae and Their Attraction to Preferred Food Sources: Pengaruh Kualitas dan Kuantitas Makanan terhadap Perilaku Kanibalisme pada Tribolium Castaneum Dewasa terhadap Larva dan Ketertarikannya pada Sumber Makanan yang Disukai - Khudhier, Hasnaa Talib; Jawad, Huda Noori; Jabbar, Hussain Ali (Universitas Muhammadiyah Sidoarjo, 2025)
The current study aims to scrutinize the qualitative and quantitative impacts of three essential food types which are wheat flour, dry milk, and mays starch on the cannibalism process of the adult Tribolium castaneum and their larvae, and to identify the food type that is preferable for trapping and attracting adults during different periods of time. The results of the main effects showed that there are significant differences between the three food types in regard to their impact on the average survival rate. The average of surviving larvae is ranged from 9.3 larvae for wheat flour to 2.6 and 2.3 larvae for dry milk and mays starch treatments, respectively. The highest larval survival was at a concentration of 5 grams of wheat flour, while the lowest survival appeared to be at a concentration of 0.2 grams of dry milk and mays starch. During the first week, the highest number of surviving larvae was recorded, whereas the lowest one was observed in the fourth week; the survival rates were 7.0 and 2.0 respectively. In respect with the findings of the trapping and attraction of adult insects, wheat flour appeared to be the most attractive food type for adults, with an average of 50.2 insects if compared to 5.0 and 2.7 insects for dry milk and mays starch treatments, respectively. As for the average effect of time periods, the highest attraction took place on day five, with an average of 25.7 insects, while the lowest was recorded on day one, with an average of 10.6 insects. It was noticed that there was variation of the interaction effect; the highest average was observed on day five, while wheat flour treatment attracted 70.3 insects. On the contrary, the lowest effect for mays starch and dry milk treatments were recorded on the 4th and 5th days, with only an average of 2.5 insects attracted. Such findings highlight the significance of food type and food quantity in modifying predation behavior and adult attraction of Tribolium castaneum. Highlights: Survival: Wheat flour supports highest larval survival; dry milk and starch lowest. Attraction: Wheat flour attracts most adults, peaking at 70.3 insects on day five. Impact: Food type and quantity influence predation and adult attraction behavior. Keywords: E Cannibalism, Tribolium castaneum, Flour condition.